Individual Case Safety Reports Analysis for Patients with Diabetes Mellitus on Insulin in Africa and the Middle East - Mlotshwa, Charity R.N.; Burger, Johanita R.; Vorster, Martine; Rakumakoe, Dorcas M.; Cockeran, Marike (Current Drug Safety, 2022)
Background: The growing numbers of patients with diabetes mellitus in Africa and the Middle East on antidiabetic therapies necessitate an understanding of adverse event (AE) reporting in these regions. Objective: The aim of the study was to provide an AE reporting overview in patients using insulin in Africa and the Middle East by characterizing and comparing individual case safety reports (ICSRs) features. Methods: The cross-sectional study analyzed ICSR data from a global pharmaceutical company’s pharmacovigilance database for January to December 2018 to describe and compare patient demographics, report sources, reporter types, ICSR seriousness, suspect products, indication for insulin use and AE preferred terms, by country. Results: Overall 7076 ICSRs were analyzed, 63.6% from the Middle East. Most ICSRs were nonserious (91.5%), from solicited sources (83.5%), and reported by consumers (70.7%). Patients from the Middle East were, on average, 34.2 years of age, had gestational diabetes mellitus as indication (64.3%), insulin detemir as suspect product (76.5%), and exposure during pregnancy as AE preferred term (89.1%). Patients from Africa were 48.1 years old on average, a higher proportion of type 2 diabetes mellitus was observed (52.2%), human insulin was the suspect product (51.6%), and blood glucose increased the AE preferred term (23.1%). Few macrovascular and microvascular complications were reported (< 1% in both regions). Associations between the region and patient age, gender, report sources, reporter types, indications for insulin use, suspect products, and AE preferred term were significant (p < 0.001). Conclusion: ICSRs features were region-specific and dependent on patient age, gender, report sources, reporter types, suspect products, and AE preferred terms.
Keywords: adverse event reporting